Zawartość fosforanów w pyle drogowym w Zielonej Górze = The phosphate content in the street dust in Zielona Gora - Walczak, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of investigations about content phosphate in the street dust in Zielona Gora. The samples of street dust were taken two times (during the winter and spring) from 56 points of city roads. Noticeable is higher phosphate content in road dust samples collected in winter than in samples taken during the spring.
Keywords: fosforany; pyły drogowe; phosphate; street dust